(untitled) (European Journal of Interdisciplinary Research and Development, 2022)
The article investigates the issues of the economic essence and features of increasing the capitalization of commercial banks. Also, some issues of increasing the capitalization of commercial banks in the context of the introduction of innovations are considered, scientific conclusions, proposals and recommendations of the authors on increasing the capitalization of commercial banks in the context of the introduction and development of innovations in the economy are formulated.